2009
DOI: 10.1016/j.ajhg.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for Purifying Selection: An Improved Human Mitochondrial Molecular Clock

Abstract: There is currently no calibration available for the whole human mtDNA genome, incorporating both coding and control regions. Furthermore, as several authors have pointed out recently, linear molecular clocks that incorporate selectable characters are in any case problematic. We here confirm a modest effect of purifying selection on the mtDNA coding region and propose an improved molecular clock for dating human mtDNA, based on a worldwide phylogeny of > 2000 complete mtDNA genomes and calibrating against recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
915
12
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 658 publications
(1,008 citation statements)
references
References 121 publications
(159 reference statements)
51
915
12
16
Order By: Relevance
“…This has been detected previously in mtDNA phylogeny (younger mutations are enriched in the first type, so that they often define branch tips) and a lot of debate on the selective pressures acting upon is ongoing [11][12][13][14][15][16] (and was also detected in animal models as our group has shown in lab mouse 17 ). The issue is, however, extraneous to the topic and goals of our paper; we can nevertheless clarify, as requested, that the finding does not result from a 'special clinical population of subjects'.…”
supporting
confidence: 65%
“…This has been detected previously in mtDNA phylogeny (younger mutations are enriched in the first type, so that they often define branch tips) and a lot of debate on the selective pressures acting upon is ongoing [11][12][13][14][15][16] (and was also detected in animal models as our group has shown in lab mouse 17 ). The issue is, however, extraneous to the topic and goals of our paper; we can nevertheless clarify, as requested, that the finding does not result from a 'special clinical population of subjects'.…”
supporting
confidence: 65%
“…We used a constant linear function of population size change, the HKY substitution model with a gamma site heterogeneity model, and a strict clock with a mean substitution rate of 9.883E − 8 substitutions/site/year. 42 Results reported were based on three independent runs showing identical results, with values of effective sample sizes higher than 200 for the parameters of interest, and after the visual evaluation of the convergence of the chains in stationary distributions by using the software Tracer v.1.6. 43 Indian geographic areas were tested as putative origins for Roma lineages.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…43 The ages of the lineages G2a2 (further defined by mutation 16193 and named G2a2 tentatively) and M9a1a2a (characterized by mutations 16145, 16316 and a back mutation at site 16362, and designated as M9a1a2a) (Table 4) were estimated by using the r statistic 44,45 with the suggested calibration rates. 44,46 RESULTS AND DISCUSSION On the basis of the combined information from control-region and partial coding-region segments, the majority (96.34%; 237/246) of the Nepalese mtDNAs could unambiguously be allocated into the defined haplogroups of East Eurasian (36.59%; 90/246), 1,[20][21][22][23][24][25] Table S1, Supplementary Material online), 5 and this pattern remains almost stable for both the East Eurasian (45.11%; 189/419) and South Asian (47.49%; 199/419) components after taking into account the recently reported Nepalese mtDNA data. 5 As for the 21 samples with ambiguously phylogenetic status, completely sequencing their mtDNA genomes revealed that virtually all of these samples in fact belong to the already defined haplogroups, such as M3, M5, M18, M30, M35, M43, D4, R8 and M60.…”
Section: Resultsmentioning
confidence: 99%
“…Among the five Nepalese populations under study, three clustered with the Tibetans (Figure 3). After we considered all the Nepalese regional populations as a whole and calculated its Table 4 Estimated ages of haplogroups G2a2 and M9a1a2a based on the calibration rates proposed in Forster et al 44 and Soares et al 46 Soares et al's rate 46 Forster et al's rate 44 Haplogroup N r ± s T (ky) r ± s T (ky) …”
Section: Resultsmentioning
confidence: 99%